Direct Electrochemical Detection of Trace Porcine Insulin on Carbon Paste Electrode with Modified Graphite Powder - Guo, C.Z.; Chen, C.G.; Luo, Z.L.; Zhao, A.D. (Asian Journal of Chemistry, 2012)
Macromolecular organic species generally shows slow electron-transfer rate and produces insensitive redox peaks on solid electrodes. In this work, electrochemical behaviour and analytical detection of porcine insulin were performed using carbon paste electrode. It was found that insulin could adsorb on the carbon paste electrode surface effectively, which resulted in the enhancement of its direct electron transfer rate. Furthermore, insulin exhibited a sensitive anodic peak at about +0.5 V on the carbon paste electrode and its electrochemical process is irreversible completely. Under the optimized conditions (i.e. 5 × 10-3 M sodium carbonate supporting electrolyte with pH 10.50, 30 % paraffin oil and 70 % graphite powder for F = 2.5 mm electrode, accumulation at the open-circuit potential for 60 s), the anodic peak current was good linear to insulin concentration in the range from 50 to 700 nM with a correlation coefficient of 0.997. The limit of detection was calculated to be 10 nM (S/N = 3). This result was successfully applied to the determination of insulin in medical injection and the recovery was 96.4-104.3 %.